Sentidos, regulações e práticas de plataformização do trabalho em Portugal - Hermes Augusto Costa; José Soeiro; Vamberto Miranda Filho (Revista Crítica de Ciências Sociais, 2022)
This text aims to contribute to a better understanding of the crowd-sourcing paradigm, i.e., the use of subcontracting atomized individuals. To this end it is necessary to identify some of the constraints that restrict work mediated by digital platforms, to systematize their characteristics and ongoing processes. Such processes dialogue with claiming and organizing logics associated with concrete experiences and identities. Based on an analysis of normative documents, grievance sheets, manifestos and interviews with leaders of unions and workers’ movements on digital platforms, the focus is on PHV drivers and food delivery couriers. It is argued that those protagonists of recent struggles in Portugal express distinct labor identities in a field where regulatory processes, protest agendas and forms of collective self-identification confront and influence each other reciprocally.